Structure of university students’ view of mathematics in Estonia - Kaldo, Indrek; Hannula, Markku (NOMAD Nordic Studies in Mathematics Education, 2012)
This study reports on first-year Estonian university students’ view of mathematics. The data was collected from 970 university students of different disciplines. The participants filled out a Likert-type questionnaire that was developed using previously published instruments. The study confirmed that several different attitudes, beliefs, and motivational orientations can be identified and validly measured as separate components of Estonian university students’ view of mathematics. However, the low reliability of some scales highlights the necessity for careful testing of instruments in any new population.